1990
DOI: 10.1007/bf00370214
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of calcium-activated chloride conductance in Xenopus oocytes: roles of calcium and protein kinase C

Abstract: Inactivation of Ca2(+)-induced Cl- currents was studied in Xenopus oocytes using the two-electrode voltage-clamp technique. In oocytes permeabilized to Ca2+ by treatment with the ionophore A23187, Ca2+ influx caused by the addition of 2.5-5 mM Ca2+ to the extracellular solution elicited Cl- currents consisting of two components: a fast, transient one (Ifast) and a slow one (Islow). In response to a subsequent application of the same dose of Ca2+, Ifast and Islow were reduced (inactivation phenomenon). The inac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

1990
1990
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(17 citation statements)
references
References 27 publications
2
15
0
Order By: Relevance
“…Traces recorded from non-injected oocytes treated with PMA showed a reduction in the fast initial spike current, but the sustained current was still observed (data not shown). This finding indicates that the fast Ca 2+ -activated Cl --current component was inhibited by PMA treatment, whereas the slowly progressing Cl --current component was unaffected, in accordance with previously published data [28]. Thus, based on these data, it cannot be excluded that part of the effect of PMA could reflect an effect of PKC on the Cl -channels responsible for the initial fast current; however, it is unlikely that the PMA treatment affects the Cl -channels responsible for the prolonged Cl -current.…”
Section: +supporting
confidence: 82%
“…Traces recorded from non-injected oocytes treated with PMA showed a reduction in the fast initial spike current, but the sustained current was still observed (data not shown). This finding indicates that the fast Ca 2+ -activated Cl --current component was inhibited by PMA treatment, whereas the slowly progressing Cl --current component was unaffected, in accordance with previously published data [28]. Thus, based on these data, it cannot be excluded that part of the effect of PMA could reflect an effect of PKC on the Cl -channels responsible for the initial fast current; however, it is unlikely that the PMA treatment affects the Cl -channels responsible for the prolonged Cl -current.…”
Section: +supporting
confidence: 82%
“…However, in the latter case, we studied the hypothesis of a feedback inhibition via PKC* [63]. We found that both regulations are not essential (Figure 5B).…”
Section: Discussionmentioning
confidence: 93%
“…Although ionomycin renders the plasma membrane somewhat leaky to Ca 2ϩ , in Xenopus oocytes this effect is very small, and the resulting Ca 2ϩ influx is very slow and cannot be confused with the robust effect of store depletion caused by ionomycin or other Ca 2ϩ ionophores (Boton et al, 1990). Suppression in InsP 3 -Ftreated cells reached 77 Ϯ 4.8% (n ϭ 14), and the recovery reached 50% after 28 min (n ϭ 8).…”
Section: D When Camentioning
confidence: 93%
“…However, whereas the initial transient reflects only Ca 2ϩ release, the oscillations reflect release and reuptake of Ca 2ϩ into the InsP 3 -sensitive stores (Lechleiter et al, 1991;Jafri et al, 1992). Also, the initial transient and oscillations have different properties, probably reflecting Ca 2ϩ release from different pools (Gillo et al, 1987) or different gating mechanism of I C l,C a (Boton et al, 1990). When experiments similar to those of Figure 1 A were undertaken without external Ca 2ϩ the prolonged current and oscillations were very similar to those of Figure 1 A (n ϭ 16).…”
Section: -Apb Blocks the Inositol-lipid Signaling Of Xenopus Oocytesmentioning
confidence: 99%